Pengaruh Profitabilitas, Ukuran Perusahaan, Tangibility, Risiko Bisnis terhadap Struktur Modal pada Perusahaan Indeks SRI-KEHATI - Givari, Muhammad Arbiant; Yantiana, Nella; Rusmita, Sari; Noviarty, Helisa (Journal of Innovation in Management, Accounting and Business, 2024)
This research aims to explore how the capital structure of companies with a strong commitment to sustainability can be influenced by factors such as profitability, firm size, tangibility, and business risk. These companies support environmental sustainability initiatives. This study is included in the category of quantitative research. The Data used is secondary data. The population in this study consists of companies listed on the Indonesia Stock Exchange and included in the Sustainable and Responsible Investment (SRI)-KEHATI index over a five-year period, from 2019 to 2023. The sampling technique used is purposive sampling based on specific criteria, resulting in 11 companies selected as the research sample. The number of observations used is 55. Data analysis techniques using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that the capital structure of the studied companies is not influenced by profitability and business risk, but it is significantly influenced by tangibility and firm size.